1998
DOI: 10.1021/ja973282k
|View full text |Cite
|
Sign up to set email alerts
|

Alkene Complexes of Divalent and Trivalent Ruthenium Stabilized by Chelation. Dependence of Coordinated Alkene Orientation on Metal Oxidation State

Abstract: Zinc amalgam reduction of tris(acetylacetonato)ruthenium(III), [Ru(acac)3], in the presence of the chelating olefinic N- and O-donor ligands (LL‘) 2-vinyl-N,N-dimethylaniline, o-CH2CHC6H4NMe2 (1), 2-isopropenyl-N,N-dimethylaniline, o-CH2C(CH3)C6H4NMe2 (2), 3-butenyldimethylamine, CH2CHCH2CH2NMe2 (3), 2-allylpyridine, CH2CHCH2C5H4N (4), isomesityl oxide (4-methyl-4-penten-2-one), CH2C(CH3)CH2COCH3 (5), 2-methoxystyrene, o-CH2CHC6H4OMe (6), and 3-butenylmethyl ether, CH2CHCH2CH2OCH3 (7) gives the correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 59 publications
4
21
0
Order By: Relevance
“…The two d N–N bond lengths in the complex 4 are 1.309(3) and 1.300(2) Å. The Ru–O bond lengths in complex 4 are 2.0428(17) and 2.0821(15) Å, which are commonly observed in the other Ru­(II)–acac complexes. The ligand DTBCat coordinates via deprotonation and can exists in different oxidation states (catecholate, semiquinone, and quinonoid), C–O bond length of the coordinated ligand is an indicator of its oxidation state.…”
Section: Resultsmentioning
confidence: 73%
“…The two d N–N bond lengths in the complex 4 are 1.309(3) and 1.300(2) Å. The Ru–O bond lengths in complex 4 are 2.0428(17) and 2.0821(15) Å, which are commonly observed in the other Ru­(II)–acac complexes. The ligand DTBCat coordinates via deprotonation and can exists in different oxidation states (catecholate, semiquinone, and quinonoid), C–O bond length of the coordinated ligand is an indicator of its oxidation state.…”
Section: Resultsmentioning
confidence: 73%
“…[Note that although this orbital is bonding ] z (z = 0 and 1). 9 The Dewar-Chatt-Duncanson model 10 for metal-alkene bonding accounts for the difference in that oxidation will result in depopulation of a metal-alkene π-bonding orbital (either directly, or indirectly by depopulation of a metal orbital). Oxidation therefore inhibits metal-to-alkene π-back donation and the metal-alkene bond is weakened and lengthened.…”
Section: Dalton Full Papermentioning
confidence: 99%
“…A 17-18-19-electron triad of stable isostructural organometallic FeCp complexes has been presented by Astruc and co-workers, [10] and Bennett et al have reported a series of air-stable ruthenium alkene complexes with 17 and 18 electrons. [17] Although significant progress has been made recently, it is probably fair to say that tools for the comprehensive study of paramagnetic organometallic species are by far not as well established as for coordination compounds. This includes spectroscopic techniques in solution as well as computational work.…”
Section: Introductionmentioning
confidence: 99%